2014
DOI: 10.1007/s11240-014-0634-x
|View full text |Cite
|
Sign up to set email alerts
|

Potato virus X displaying the E7 peptide derived from human papillomavirus type 16: a novel position for epitope presentation

Abstract: Potato virus X (PVX) is widely used as a peptide presentation system in plant biotechnology, mostly by fusion of desired peptides to the N-terminus of its capsid protein (CP). Considering that some epitopes can interfere with the stability and/or self-assembly of PVX CP when fused to its N-terminus, we evaluated four other possible sites for fusion using the E7 epitope derived from human papillomavirus type 16 with different tags. We prepared eight different PVX CP constructs modified with the E7 epitope fused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this paper, we extend our previous work on transient expression in plants using plant virus-based vectors (Cerovska et al 2008(Cerovska et al , 2013Vaculik et al 2015). Here, we focus on both transient expression and co-expression of two proteins in BY-2 cells, which had earlier been described in whole plants (Chen et al 2011;Huang et al 2010;Montague et al 2011;Sainsbury et al 2009).…”
Section: Introductionmentioning
confidence: 85%
“…In this paper, we extend our previous work on transient expression in plants using plant virus-based vectors (Cerovska et al 2008(Cerovska et al , 2013Vaculik et al 2015). Here, we focus on both transient expression and co-expression of two proteins in BY-2 cells, which had earlier been described in whole plants (Chen et al 2011;Huang et al 2010;Montague et al 2011;Sainsbury et al 2009).…”
Section: Introductionmentioning
confidence: 85%
“…Vaculik et al (2015a) identified four promising internal transgene insertion positions within the surface loops of the PVX CP. The tested epitope insertion mutant was infectious and produced particles only after amino acid 23 (Vaculik et al, 2015b). However this position still belongs to the N-terminal intrinsically disordered domains of Potexviruses (Solovyev and Makarov, 2016) and is therefore not essential for particle assembly.…”
Section: Master Of Puppets: Strategies For the Creation Of Modified Pmentioning
confidence: 99%
“…Studies performed by fusing peptides (variable in length and amino acid composition) to a N-terminally truncated CP (a natural PVX mutant lacking the first 21 amino acids) have indicated that also isoelectric point, Ser/Thr and Trp content in the heterologous sequence may affect viral fitness ( Lico et al, 2006 ). Recently, the insertion of a heterologous sequence between amino acids 23 and 24 at the N-terminus of the CP has also been reported ( Vaculik et al, 2015 ). Nonetheless, up to now no CP domains other than the N-terminus have been identified that can harbor fusion peptides/proteins.…”
Section: Pvx Nanoparticles For Subunit Vaccine Deliverymentioning
confidence: 99%